Elderly Friendly City Concepts and Indicators - Fatemeh Estebsari; Zahra RahimiKhalifeh Kandi; Kimya Estebsari; Davoud Mostafaei (Iranian Association of Health Education and Health Promotion, 2020)
Population aging and urbanization are two global trends that together form one of the challenges of the 21st century. The purpose of this study was to the concept of age friendly city and its indicators. The findings of the study were classified into three areas of the history of the age friendly city, the definition of the age friendly city, the age friendly city indicators and Programs, and the content of each of the Indicators. The findings of this study can be considered as the basis for designing elderly friendly cities in order to improve the quality of life of the elderly and promote active aging. In this regard, it is necessary to pay special attention to the appropriateness of the criteria with the cultural and social conditions in Iran Type of Study: Editorial